Mengelola Sampah Menjadi Pupuk di Desa Labuan Kecamatan Lage Kabupaten Tojo Una-Una - Indro Subagyo; Hasanudin, Hasanudin; Saharudin, Saharudin (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
Article History: Received: Revised: Accepted: Abstract: The concept of community-based waste management must be accompanied by community empowerment. community empowerment in this case is making the community have the power or power to be able to manage waste so that it becomes something useful and worth selling. Empowerment refers to the ability of people so that they have the ability to meet basic needs, increase income, and to be able to participate in the development process. The purpose of this service is to create a green and clean village packaged in a community service package by the team of lecturers from the Poltekkes Kemenkes Palu. Activity Steps The activity steps carried out are intensive training through the following stages: 1. Lectures on the study of waste management systems. 2. Lectures on managing and processing household waste, especially the 3R method of composting (Reduce, Reuse, Recycle). 3. Demonstration on the implementation of the Garbage Bank. 4. Practice segregating waste and applying composter. 5. Consultation in overcoming some of the obstacles faced by participants in household waste management. 6. The culture of mutual cooperation in the community Keywords: Gerbage, composter, reduce, reuse, recycle